Understanding the transition to motherhood among adolescent mothers in rural Pakistan: Implications for mental health - Amber Hussain; Tanya Park; Zahid Ali Memon; Salima Meherali (PLoS ONE, 2026)
Purpose This study explored how adolescent mothers in Pakistan experience the transition to motherhood and the mental health challenges that arise during this period. Methods A focused ethnographic study was conducted with 25 adolescent mothers in Matiari, Sindh. Data were collected through semi‑structured interviews, participant observations, and artifact elicitation. Meleis’ Transition Theory informed the study focus and development of the interview guide. Reflexive thematic analysis guided interpretation, informed by an intersectional lens. Findings Five themes described mothers’ experiences: early educational disruption and redirected aspirations; continuous caregiving with uneven support; barriers to maternal healthcare access; emotional distress and psychological strain; and identity transformation. These intersecting challenges contributed to significant mental health strain and highlighted persistent gaps in access to supportive, adolescent-responsive maternal care. Conclusions Adolescent mothers navigate motherhood with substantial emotional and practical burdens yet demonstrate meaningful resilience. Findings highlight the need for adolescent‑responsive mental health support, accessible care, routine and confidential distress screening, referral pathways, and supportive educational and community‑based interventions tailored to underserved rural settings.